2014
DOI: 10.1136/openhrt-2014-000101
|View full text |Cite
|
Sign up to set email alerts
|

ECG characteristics according to the presence of late gadolinium enhancement on cardiac MRI in hypertrophic cardiomyopathy

Abstract: BackgroundLate gadolinium enhancement (LGE) on cardiac MRI (CMR) has been described as an independent predictive factor of cardiovascular events among patients with hypertrophic cardiomyopathy (HCM). LGE and Q waves are considered as myocardial scar markers but their relation in the context of HCM is poorly established and has to be more supported. The objective of the study was to compare ECG findings in the presence or absence of LGE.Methods42 patients with HCM confirmed by CMR were included in the study. EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The main finding of this study is low sensitivity (14.3%–40.8%) of each respective ECG criteria of LVH. This may be surprising in presence of extensive hypertrophy confirmed in TTE; however, it is consistent with results of several studies (Dohy et al, 2020 ; Erice et al, 2009 ; Grall et al, 2014 ; Tangwiwat et al, 2019 ). Majority of those analyzes took into consideration only Sokolow‐Lyon Index and Cornell Voltage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main finding of this study is low sensitivity (14.3%–40.8%) of each respective ECG criteria of LVH. This may be surprising in presence of extensive hypertrophy confirmed in TTE; however, it is consistent with results of several studies (Dohy et al, 2020 ; Erice et al, 2009 ; Grall et al, 2014 ; Tangwiwat et al, 2019 ). Majority of those analyzes took into consideration only Sokolow‐Lyon Index and Cornell Voltage.…”
Section: Discussionsupporting
confidence: 90%
“…Dohy et al suggested that fibrosis of myocardium may be connected with lower QRS amplitude in corresponding leads (Dohy et al, 2020 ). Conversely, Grall et al did not find relation between LGE and QRS amplitude (Grall et al, 2014 ). We showed that combination of two or three criteria highly increases sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…Others, by correlating ECG findings with echocardiogram first and LGE-CMR later suggested that lateral Q waves might be secondary to an abnormal activation of the hypertrophied septum rather than fibrosis [6], [13], [18]. This hypothesis was also recently supported by a French study of 42 patients [19]. Negative T waves have been correlated with a specific pattern of apical hypertrophy extremely common in Asia (25% of cases) called “Japanese variant” ascribing the pathogenesis of such ECG abnormalities to a chronic ischaemia and fibrosis replacement [20].…”
Section: Discussionmentioning
confidence: 87%
“…A previous study in an adult population study by Grall et al 23 described a correlation between Q waves on ECG and LGE presence. Unlike this and other previous adult studies,24 25 while pathological Q waves, T wave changes and ST segment changes were commonly found in patients with LGE, we found no significant difference in frequency compared with patients without LGE in this paediatric population.…”
Section: Discussionmentioning
confidence: 86%
“…In this population, we found that the presence of LGE was associated with significantly increased septal thickness yet paradoxically decreased precordial voltages on ECG. Previous studies have reported on the relationship between abnormal ECG findings and phenotypical expression of HCM22 and presence of LGE23 in adults. To our knowledge, this is the first report on the effect of LGE presence in HCM on LV precordial voltage on ECG in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%